e-Mathscore: score at your fingertips - Lim, Hwee Cheng; Mat Daud, Nurul Dasila; Huzir, Sarah Iylia; Muhammad Ghazali, Sarah Afifah; Ismail, Nur Afika (Academica Press Solutions, 2024)
The e-Mathscore innovation addresses the challenge of efficiently managing and monitoring Summative Assessment Test (UPS) and Continuous Assessment (PB) scores in mathematics education through data analysis technology. By leveraging the capabilities of Google Data Studio and Google Spreedsheet, e-Mathscore provides a systematic platform for lecturers, students, and parents to access and review assessment scores. Originating from the online Matriculation Program Semester Examination (PSPM) results checking system, e-Mathscore offers an intuitive solution for enhancing student self-awareness and improving teaching and learning (PdP) productivity for lecturers. With its user-friendly interface, e-Mathscore facilitates easy access for students and parents, thereby reducing paper usage and streamlining the assessment process. The innovation demonstrates significant potential for commercialization, as it addresses a critical need in the education sector and offers scalability for implementation across various subjects and matriculation colleges in Malaysia. Moreover, the system's ability to provide comprehensive insights into student performance, along with features like the PSPM target meter, further underscores its impact on educational outcomes. Overall, e-Mathscore represents a transformative solution poised to revolutionize mathematics education and improve learning experiences for students and educators alike.